Dynamic Analysis of Two-lane Skewed Bridge and High-speed Train System - Jahangiri, Meysam; Zakeri, Jabar-Ali (Periodica Polytechnica Civil Engineering, 2019)
Bridges are vital in the operation of railway networks since any hindrances to their operation could suspend the flow of traffic. An important characteristic of bridges highly affecting their behavior is the skew angle. In this paper, a sensitivity analysis is performed to identify the effects of skew angle on train-track interaction for single- and double-sided crossings of a high-speed train. Comprehensive three-dimensional finite element models of the bridge and vehicle are developed, which are then calibrated using dynamic field test results. Effects of skew angle on shape modes and modal frequencies, acceleration values, and bridge displacement in various crossing speeds are studied. The results showed that if the bridge skew angle is more than 15°, it will affect the modal shape and frequency of the bridge. When the skew angle is less than 15°, the results of the bridge displacement are similar to those of the bridge with skew angle of zero. However, with the increase of the skew angle, the deformation value of the bridge decreases and the speed corresponding to the maximum displacement value also varies. Finally, the results of acceleration due to the speed and skew angle of the bridge are not the same in one-way and two-way passing states.